Overcoming Ostrea edulis seed production limitations to meet ecosystem restoration demands in the UN decade on restoration - Ermgassen, Philine S.E. zu; Strand, Åsa; Bakker, Nienke; Blanco, Ainhoa; Bonačić, Kruno; Boudry, Pierre; Brundu, Gianni; Cameron, Tom C.; Connellan, Iarfhlaith; Da Costa, Fiz; Debney, Alison; Fabra, Mónica; et al. (Aquatic Living Resources, 2023)
The European flat oyster, Ostrea edulis, is a habitat-forming bivalve which was historically widespread throughout Europe. Following its decline due to overfishing, pollution, sedimentation, invasive species, and disease, O. edulis and its beds are now listed as a threatened and/or declining species and habitat by OSPAR. Increasing recognition of the plight of the oyster, alongside rapidly developing restoration techniques and growing interest in marine restoration, has resulted in a recent and rapid growth in habitat restoration efforts. O. edulis seed supply is currently a major bottleneck in scaling up habitat restoration efforts in Europe. O. edulis has been cultured for centuries, however, research into its culture declined following the introduction of the Pacific oyster, Crassostrea gigas to Europe in the early 1970 s. Recent efforts to renew both hatchery and pond production of O. edulis seed for habitat restoration purposes are hampered by restoration project timelines and funding typically being short, or projects not planning appropriately for the timescales required for investment, research-and-development and delivery of oyster seed by commercial producers. Furthermore, funding for restoration is intermittent, making long-term commitments between producers and restoration practitioners difficult. Long-term, strategic investment in research and production are needed to overcome these bottlenecks and meet current ambitious restoration targets across Europe. This work was the product of the Production Working Group within the Native Oyster Restoration Alliance (NORA). The NORA Secretariat are funded by the Federal Ministry for the Environment, Nature Conservation and Nuclear Safety and the German Federal Agency for Nature Conservation (Bundesamt für Naturschutz) through the Federal Program for Biodiversity and the Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research within the project PROCEED (FKZ 3517685013). PSEzE is supported by The Nature Conservancy, Global Ocean Team. Peer ...